2008
DOI: 10.1175/2008mwr2360.1
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic and Moisture Characteristics of a Nonprecipitating Cold Front Observed during IHOP. Part II: Alongfront Structures

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 66 publications
1
7
0
Order By: Relevance
“…Weckwerth and Wakimoto (1992) documented a case in which intersections between a gust front and horizontal vortex lines associated with Kelvin-Helmholtz (K-H) waves with wave crests oriented nearly perpendicular to the gust front produced updraft maxima along the gust front. Similar intersections of horizontal vortex lines and a cold air leading edge were also reported for a nonprecipitating cold front studied by Friedrich et al (2008). The phase lines of the vertical velocity perturbation for U5-S1 are oriented nearly perpendicular to the direction of the mean vertical shear.…”
Section: ) Stably Stratified Casessupporting
confidence: 80%
See 1 more Smart Citation
“…Weckwerth and Wakimoto (1992) documented a case in which intersections between a gust front and horizontal vortex lines associated with Kelvin-Helmholtz (K-H) waves with wave crests oriented nearly perpendicular to the gust front produced updraft maxima along the gust front. Similar intersections of horizontal vortex lines and a cold air leading edge were also reported for a nonprecipitating cold front studied by Friedrich et al (2008). The phase lines of the vertical velocity perturbation for U5-S1 are oriented nearly perpendicular to the direction of the mean vertical shear.…”
Section: ) Stably Stratified Casessupporting
confidence: 80%
“…Many studies have demonstrated that misocyclones along air mass boundaries distort the boundaries and produce local maxima of low-level convergence and vertical velocity in their vicinity, which often could be preferred regions to form clouds and/or radar reflectivity cores (e.g., Wilson et al 1992;Atkins et al 1995;Lee and Wilhelmson 1997b;Friedrich et al 2005;Arnott et al 2006;Murphey et al 2006;Marquis et al 2007;Wakimoto and Murphey 2009). Although well-defined vortices with quasi-circular vorticity contours do not develop in the present simulations, it is suggested that in the U15-S2 and U20-S2 cases the concentrated vertical vorticity distorted the horizontal wind field and enhanced the low-level convergence in the vicinity of the vorticity maxima, leading to formation of the precipitation maxima north of the bow apexes.…”
Section: ) Stably Stratified Casesmentioning
confidence: 99%
“…Initially studied and documented by fluid dynamicists Helmholtz (1868) and Lord Kelvin (1871), later studies were done using both visual (Ludlam 1967;Reiss and Corona 1977) and laboratory observations (Drazin 1958;Thorpe 1968Thorpe , 1971Thorpe , 1973Simpson 1969Simpson , 1982Scotti and Corcos 1972;Britter and Simpson 1978;Koop and Browand 1979). As technology advanced, K-H waves were also observed by an assortment of instrumentation including ground-based radars (Hicks and Angell 1968;Browning and Watkins 1970;Mueller and Carbone 1987;Weckwerth and Wakimoto 1992;Chapman and Browning 1997;Petre and Verlinde 2004;Luce et al 2008) and airborne radars equipped with additional instrumentation (Browning et al 1973, Hardy et al 1973Wakimoto et al 1992;Wakimoto and Bosart 2001;Friedrich et al 2008;Geerts and Miao 2010), and were numerically simulated (Fritts 1979;Sykes and Lewellen 1982;Droegemeier and Wilhelmson 1986;Fritts et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Individual case studies in the literature suggest numerous environments in which KH instability can be released: KH waves (or ''billows'' as they are commonly referred to) have been observed in or near cumulonimbus anvils (Petre and Verlinde 2004;Trier 2016), near the tropopause (Mahalov et al 2011;Trier et al 2012), at the base of low-level jets (e.g., Nakanishi et al 2014;Lin et al 2019), near the top of density currents associated with a sea breeze (Sha et al 1991), behind a cold front (Geerts et al 2006;Friedrich et al 2008;Samelson and Skyllingstad 2016), at the upper boundaries of other cold-air intrusions (Zhou and Chow 2013), in midlatitude cyclones (Wakimoto et al 1992), and above mountainous terrain (Geerts and Miao 2010;Medina and Houze 2016).…”
Section: Introductionmentioning
confidence: 99%